Body care of older people in different institutionalized settings: A systematic mapping review of international nursing research from a Scandinavian perspective. Issue 1 (6th June 2022) - Rosendal, Kirstine A.; Lehn, Sine; Overgaard, Dorthe
Abstract: Body care is considered a key aspect of nursing and imperative for the health, wellbeing, and dignity of older people. In Scandinavian countries, body care as a professional practice has undergone considerable changes, bringing new understandings, values, and dilemmas into nursing. A systematic mapping review was conducted with the aims of identifying and mapping international nursing research on body care of older people in different institutionalized settings in the healthcare system and to critically discuss the dominant assumptions within the research by adapting a problematization approach. Most identified papers reported on empirical research with a biomedical approach focusing on outcome and effectiveness. Conceptual papers, papers with a focus on the perspectives of the older people, or contextual and material aspects were lacking. The research field is dominated by four dominant assumptions: Body care as an evidence‐based practice, body care as a relational ethical practice, the body as a body‐object and a body‐subject, the objects in the body care practices as nonrelational materialities . Given the complexities of professional body care practices, there is a need for other research designs and theoretical perspectives within nursing that expand our understanding of body care taking into consideration the multiple social and material realities.